KEMAMPUAN MENULIS TEKS ULASAN CERPEN SISWA KELAS VIII SMP - Waode Nur Azizah; Fahruddin Hanafi; Marwati (PT. CASA CENDEKIA MEDIA, 2024)
The study's objective was to describe the ability of class VIII students at SMP Negeri 1 Lasalepa to write short story review texts. This study employed a quantitative descriptive approach. The participants in this study were all 106 eighth-grade students from four classes at SMP Negeri 1 Lasalepa. To choose the sample that will be used in this study, we used the stratified proportional random sampling method, which involves taking samples from each subpopulation that are proportional to the total number of people in that subpopulation. random. resulting in a sample size of 53 individuals for this study. The type of instrument used in this study was a test with questions about the structure and language rules of short story review texts to find out how well students could write them. A written test is the method used for data collection. In the description, the percentage technique was used, and the data analysis method was quantitatively descriptive. Out of 53 respondents, 42 (79.24%) fell into the category of being able to write short story review texts, while 11 (20.76%) fell into the category of not being able to write short story review texts in a traditional manner. The writing of short story review texts for class VIII students at SMP Negeri 1 Lasalepa falls into the incapacitated category because (79.24 percent) it did not meet the standard classical completeness requirement of 85%.